PEMETAAN PERMASALAHAN BANJIR DAN GENANGAN PADA DRAINASE PERKOTAAN BERBASIS GIS DI KOTA JAYAPURA - Kende Suma, Ratte; Mujiati; Manalu, Janviter (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2024)
The improvement in quality and normalization of drainage throughout the Jayapura City area has already beenincluded in the flood control system plan, starting from enhancing and optimizing the primary, secondary, andtertiary drainage network systems. However, suboptimal drainage conditions are still found under existingconditions, indicating that the drainage network system in Jayapura City has not yet been well optimized. Thisresearch aims to determine the strategies for managing and maintaining the drainage system in the city ofJayapura. The analysis used in this research is qualitative descriptive analysis and spatial analysis. The resultsobtained for creating flood-prone area analysis as information included in the Jayapura City Spatial Plan (RTRW),providing socialization to the community, conducting outreach to the community, and implementing spatialplanning for flood prevention.